Unmasking of Partial Diabetes Insipidus during Stress but Not Maintenance Dosing of Glucocorticoids in an Infant with Septo-Optic Dysplasia. (16th March 2011) - Puri Puri, Mala Mala; Azam Azam, Anita Anita; Loechner Loechner, Karen J. Karen J.
Abstract : Background . It is well acknowledged that glucocorticoid (GC) replacement can unmask diabetes insipidus (DI) in subjects with hypopituitarism. Objective . To increase the awareness and monitoring for transient and symptomatic DI in children with partial hypopituitarism during periods in which increased GC needs are required. Methods/Case . A 2-month-old female infant with septo-optic dysplasia (SOD; on thyroid and maintenance GC replacement therapy at 8 mg/m 2 /day) developed transient DI during 2 separate episodes of stress (one hypothermia, one febrile) when stress dosing of GC (25 mg/m 2 /day) was instituted. Conclusion . Children not diagnosed with DI during initial evaluation for hypopituitarism may benefit from rescreening of serum sodium levels during acute periods of stress that demand "stress" GC dosing. This will permit treatment and/or increased vigilance for ensuing permanent DI.